Peran Kesadaran Halal dan Efektivitas Iklan Youtube Terhadap Minat Pembelian Kosmetik Sariayu - Elvira Dewi Santika; Asep Muhamad Ramdan; Deni Muhammad Danial (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of halal awareness and advertising effectiveness on purchase intention. The data analysis technique used is multiple linear regression analysis and non-prbability sampling techniques. Data collection was done by distributing questionnaires using google form to 103 respondents in Sukabumi and data process using IBM SPSS software version 24. The simultaneously and partially halal awareness and advertising effectiveness on purchase intentions had a significant and positive effect on purchase intentions. The results of the F test, namely the value of Fcount 75,727 > 3,08 shows that Fcount is greater than Ftable and the results of the correlation in this study have a very strong value, namely 0,776 it can show that from each variable there is an influence between the halal awareness variable and the effectiveness of advertising on buying interest. The results of the t-test, which is 6.908 > 1.983, show that Tcount is greater than Ttable, so it can be concluded that the halal awareness and advertising effectiveness variables have a significant influence on buying interest.